Shape memory performance of asymmetrically reinforced epoxy/carbon fibre fabric composites in flexure - M. Fejos; J. Karger-Kocsis (eXPRESS Polymer Letters, 2013)
In this study asymmetrically reinforced epoxy (EP)/carbon fibre (CF) fabric composites were prepared and their shape memory properties were quantified in both unconstrained and fully constrained flexural tests performed in a dynamic mechanical analyser (DMA). Asymmetric layering was achieved by incorporating two and four CF fabric layers whereby setting a resin- and reinforcement-rich layer ratio of 1/4 and 1/2, respectively. The recovery stress was markedly increased with increasing CF content. The related stress was always higher when the CF-rich layer experienced tension load locally. Specimens with CF-rich layers on the tension side yielded better shape fixity ratio, than those with reinforcement layering on the compression side. Cyclic unconstrained shape memory tests were also run up to five cycles on specimens having the CF-rich layer under local tension. This resulted in marginal changes in the shape fixity and recovery ratios.